Pentingnya Konseling Lintas Agama Dan Budaya Dalam Menjaga Budaya Toleransi Di Sekolah - Diana, Fiska (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2022)
AbstracReligious difference is a necessity that gives birth to two possibilities in society, namely the potential for religious tolerance and the potential for intolerance, depending on how it is managed. Schools are the foundation in building religious tolerance, because the world of education is filled with various cultural backgrounds, even religions as well and the important thing is how a student appreciates religious tolerance in his daily life, so that in the world of education cross-religious and cultural counseling is needed, which provides direction to students so that their religious understanding does not deviate from the values of brotherhood. In general, there are several competencies that must be possessed by counselors, namely pedagogical competence, personality competence, social competence, and professional competence. Meanwhile, in the cross-cultural context, there are several awareness of multicultural counseling that must be passed by counselors for the smooth process of cross-religious-based counseling and culture, namely self-awareness, awareness of one's own culture, awareness of race, sexism, and poverty, awareness of individual differences, awareness of other cultures, awareness of diversity, skills in counseling techniques.                                                                                 Keywords: Counseling, Cross Religion and Culture, Culture of Tolerance